Discovering Educational Leadership in Connections: Dr. Elizabeth Murray of Tatamagouche - Harris, Carol (Canadian Journal of Education/Revue canadienne de l'éducation, 1994)
In recounting the educational leadership of Elizabeth Murray, with particular focus on her years as an adult educator at mid-century, I trace connections between her early years as a teacher and adult educator and her current community projects. These links are temporal, between past and present; social, between child and adult; and individual, between excellence as personal and shared experience. In writing about this woman’s early life, I discuss first the limitations of traditional historical sources to divulge significant strands of leadership action, and second, the importance of Murray’s former students and colleagues in providing essential evidence. En faisant état du leadership d’Elizabeth Murray en éducation, surtout durant les années qu’elle a consacrées à l’éducation des adultes au milieu du siècle, l’auteure établit des liens entre les premières années d’enseignante d’Elizabeth Murray auprès des enfants et des adultes et ses projets communautaires actuels: liens temporels, entre le passé et le présent; liens sociaux, entre l’enfant et l’adulte; liens personnels, entre des gens qui partagent l’expérience de l’excellence. Tout en présentant les débuts de la vie profes- sionnelle de cette femme, l’auteure discute d’abord des limites des sources historiques traditionnelles lorsqu’on cherche à dévoiler des axes significatifs de leadership en action, puis de l’importance des anciens élèves et collègues d’Elizabeth Murray, qui ont fourni des données essentielles.